Propuesta pedagógica para mejorar el ritmo en la danza folclórica en los alumnos de séptimo grado “A” de la unidad educativa “Padre Julián Lorente”, 2023 - 2024. - Ochoa Chalán, Luis Miguel (2024)
This present curricular integration work was created with the main objective of developing the improvement of folk dance rhythm through a pedagogical proposal from seventh grade students parallel “A" of “Padre Julián Lorente" educational unit; what was utilized for this study was an almost experimental Mixed Approach along with a correlational design. Also in gathering this information the methods that were applied here were the inductive, deductive, scientific, analytical and historical one. In addition, a test was performed in place for the diagnostic instrument to a group 28 students. Once verified the results that were obtained through application of the diagnostic instruments, it is pretty evident that the majority of the students that were being investigated in this study have a great deal of deficiencies when it comes to their rhythm capacity when they are performing basic folk dance steps. It was also determined that in terms of the choreographic composition, all the students are not very creative and they also show little to none improvisation of their own in order to want to execute dance steps to the rhythm of the music. These results are not entirely surprising, but much more could be done to better improved when it comes to these aspects. As a direct consequence of these results a pedagogical proposal was created as well as applied, and it was aimed at improving rhythm in folk dance and it was structured in 24 different class sessions with activities that were related to rhythm and folk dance. Right after the employment of the control instruments that were utilized in this study, there were significant improvements, which were very evident in the prior mentioned aspects. It was concluded that before the application of this Proposal, there were a number of gaps in aspects such as rhythm, temporal and spatial location, creativity, improvisation, coordination as well as balance. However, succeeding the implementation of the Proposal, these aspects were highly improved, thus, demonstrating very accurately that the program in fact is very effective and has a tremendous impact on the development of rhythm allowing the possibility of keep conducting more research of this type. Key Words: Rhythm, Folk dance, Methodology, Results, Proposal and Teaching strategy.